2020
DOI: 10.1111/jcmm.15589
|View full text |Cite
|
Sign up to set email alerts
|

Circulating exosomal long non‐coding RNAs in patients with acute myocardial infarction

Abstract: Exosomes are attracting considerable interest in the cardiovascular field as the wide range of their functions is recognized in acute myocardial infarction (AMI). However, the regulatory role of exosomal long non‐coding RNAs (lncRNAs) in AMI remains largely unclear. Exosomes were isolated from the plasma of AMI patients and controls, and the sequencing profiles and twice qRT‐PCR validations of exosomal lncRNAs were performed. A total of 518 differentially expressed lncRNAs were detected over two‐fold change, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…Another study compared the expression of lncRNAs in the peripheral blood cells between healthy and myocardial infarction patients. It demonstrated that cardiac hypertrophy-associated transcript (CHAST), MALAT1 were signi cantly upregulated in myocardial infarction patients [83][84][85]. These ndings provided a promising therapeutic strategy for acquiring atherosclerotic diseases and shed light on the clinical implication of lncRNA-associated ceRNA mechanisms in atherosclerotic disease deterioration.…”
Section: Therapeutic Use Of Lncrnas In Diseasesmentioning
confidence: 91%
“…Another study compared the expression of lncRNAs in the peripheral blood cells between healthy and myocardial infarction patients. It demonstrated that cardiac hypertrophy-associated transcript (CHAST), MALAT1 were signi cantly upregulated in myocardial infarction patients [83][84][85]. These ndings provided a promising therapeutic strategy for acquiring atherosclerotic diseases and shed light on the clinical implication of lncRNA-associated ceRNA mechanisms in atherosclerotic disease deterioration.…”
Section: Therapeutic Use Of Lncrnas In Diseasesmentioning
confidence: 91%
“…Studies have found that miR-1, miR-133a, and miR-208a are heart-specific or heart-enriched miRNAs, which can be used as reliable and sensitive markers for the early diagnosis of AMI (Chistiakov et al, 2016). Studies have also revealed that expressions of lncRNAs ENST00000556899.1 and ENST00000575985.1 in circulating exosomes are significantly increased in patients with AMI compared with those in healthy people, which can be used as potential biomarkers to predict the prognosis of patients with AMI (Zheng et al, 2020).…”
Section: Exosomal Non-coding Rnas In Coronary Artery Disease Diagnosismentioning
confidence: 99%
“…Intramedullary injection of BMSC-derived exosomes after myocardial I/R injury in mice reduces the scope of myocardial infarction and the inflammation of the myocardium and serum. Exosomes derived from MSCs change the polarization state of macrophages by reducing miR-182 expression and myocardial I/R damage in mice, also inhibiting the inflammatory response ( Zhao et al, 2019 ). Xie et al found that exosomes derived from visceral adipose tissue of high-fat diet mice (HFD-VAT) significantly induce RAW264.7 macrophage M1 phenotype transformation and proinflammatory cytokine (TNF-α and IL-6) secretion, accompanied by the enhanced phosphorylation of NF-kB-p65.…”
Section: Exosomal Non-coding Rnas In the Pathophysiology Of Coronary mentioning
confidence: 99%
“…Zheng et al found that ENST00000556899.1 and ENST00000575985.1 were significantly upregulated in circulating exosomes from AMI patients and control patients. An ROC analysis showed that ENST00000556899.1 and ENST00000575985.1 have areas under the myocardial infarction curve of 0.661 and 0.751, respectively, and are positively correlated with inflammatory biomarkers, myocardial infarction prognostic indicators, and myocardial injury markers ( 63 ). Sun et al showed that the plasma expression of the exosomal lncRNA UCA1 in patients with myocardial infarction was increased.…”
Section: Myocardial Infarctionmentioning
confidence: 99%